ASSESSMENT OF PEDESTRIAN PERCEPTION TOWARDS THE FUNCTION OF SIDEWALK SERVICES IN MAJENE REGENCY: Case Study: DR. Ratulangi, AP Pettarani and Gatot Subroto Street Banggae subdistrict - Akbar Saudi; Nur Okviyani; Ayub Pabbarang (Jurnal Infrastruktur, 2024)
Walking is the simplest form of transportation and can be used by everyone. The decline in the desire to walk is associated with the reduced service functionality of sidewalk infrastructure. This study examines pedestrian perceptions regarding the service functionality of sidewalks on DR. Ratulangi, AP. Pettarani, and Gatot Subroto streets in Banggae Subdistrict, Majene Regency. The perception assessment study uses a qualitative and quantitative descriptive statistical approach, referring to the Ministry of Public Works and Housing Regulation No. 03-2014, which provides guidelines for planning, providing, and utilizing infrastructure and pedestrian network facilities in urban areas. The analysis results indicate that the use of sidewalks is mainly driven by considerations of time and safety while walking. Respondent perceptions show that the aspects of comfort, safety, and connectivity on the streets studied fall under the